Build and Design Application of Livestock Drug Sales on Berliana Sada Mandiri - Chusnina, Ulinnuha Jaza; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Berliana Sada Mandiri (BSM) is a distributor of medicines, multivitamins and minerals for livestock. BSM sells 32 types of drugs, obtained from suppliers or manufacturers. BSM serve a variety of customers such as cooperatives (KUD), small farmers, ranchers medium, large farmers, medical assistants and veterinarians whose scattered throughout Java. A large number of customers with the different needs of drugs made warehouse staff had trouble and need a long time to serve the customer transaction and create sales reports.The problem can be solved by using the application of livestock drug sales. This application is built with waterfall method of software development models, starting from data collection, data preparation, model building applications, and build applications. Based on data collection warehouse BSM requires a database to store drugs, customers, supply of drugs, and sales transactions. Recorded data can be easily accessed again, so the warehouse staff did not take long to serve transactions, and make a report.Applications livestock drug sales may help drug record and store data, customers, and all sales transactions each day. The application can also calculate all sales transactions and generate sales reports quickly and accurately each month. So the warehouse staff did not take long to make the report.